PENGGUNAAN MEDIA SAOSIAL DAN KEBIASAAN BELAJAR SISWA DI SMK NEGERI 1 UJUNGBATU - Tisa Oktaviani; Tri Umari; Raja Arlizon (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : Data Statistics Kominfo on 2016 shows that internet usage most by individual that is for open site social media as much as 73 , 3 %. Based on the phenomenon And also several of them have been captured acces the social media where the learning process. Based on phenomenon the researchers interested for do research with the title of